Attraction of cacao mirid bug (Helopeltis bakeri Poppius) to feeding attractant β-Caryophyllene using wind tunnel behavioral bioassay - Dela Cruz, Maria Criselda V. (Animo Repository, 2021)
Theobroma cacao L. produces cocoa, the main ingredient for the production of chocolates. It is a high value agricultural crop recognized for various health benefits and due to this, the demand continues to increase. Cacao mirid bug (Helopeltis bakeri) is one of the emerging pests of cacao and it feeds and oviposit on the pods, causing lesions that renders cacao unmarketable. The use of semiochemicals is a program of IPM applied to confuse, attract, and trap pests in a biologically based way. This study aimed to evaluate the attraction of H. bakeri towards the potential feeding attractant β-Caryophyllene, determine the optimum concentration and assessed different trap designs using wind tunnel behavioral bioassays. Results showed that among treatments (45μg, 65μg, 90μg and 180μg β-caryophyllene), 90μg attracted the highest number of H. bakeri (75.05%) and was highly significant (p